2008
DOI: 10.1021/jp710505t
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Morphology of Gold Nanocrystals by Switching the Growth of {110} Facets from Restriction to Preference

Abstract: Single crystalline Au nanorods (Au NRs), synthesized via seed-mediated growth, show unique surface structures. Apart from the oft-observed {100} and {111} facets, unexpectedly, unstable {110} facets dominate in such nanorods due to {110} restricted growth. Unique properties have been suggested for the nanorods. One novel property, we believe, is that the the high-energy {110} endows the nanorod with a high reactivity, thus making the growth to more stable morphologies possible. Herein, by switching the growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
108
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(117 citation statements)
references
References 34 publications
8
108
1
Order By: Relevance
“…[ [16][17][18][19] Specifically, Au nanorods have been transformed into various shapes via overgrowth on the entire surface [16][17][18] or the side surface of Au nanorods. [19] However, this strategy has not been widely extended to noble metals other than Au.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[ [16][17][18][19] Specifically, Au nanorods have been transformed into various shapes via overgrowth on the entire surface [16][17][18] or the side surface of Au nanorods. [19] However, this strategy has not been widely extended to noble metals other than Au.…”
mentioning
confidence: 99%
“…Only recent studies by Xiang et al and Becker et al showed a system, where Ag could grow on specific sides of Au nanorods to generate nanocrystals with a semicircular or triangular morphology. [17,20] Overall, it remains a challenge to find a simple way to control the overgrowth of other metals on Au nanorods in an effort to generate bimetallic nanocrystals with a core-shell structure and the desired properties.…”
mentioning
confidence: 99%
“…The surface energy of {110} facet is higher than {100} and {111} facet, resulting in that CTAB bilayer primarily absorbed onto the {110} facet. 17,31,32 Because greater surface energy means less stability, 33 gold atoms would preferentially deposit onto the {100} and {111} facet to form rod-shaped nanoparticles. When AgNO 3 is added into the growth solution, silver ions react with bromide ions to form AgBr, which would selectively absorb onto the {110} facet of the gold nanoseeds, further inducing the gold atoms to deposit onto the {100} facet.…”
mentioning
confidence: 99%
“…Table 1. Summary of the gold nanorod size parameters in Fig.2 (final nanorods) and Fig.4 It is known that the single crystal gold nanorod has octagonal column morphology, with alternated {100} and {110} lateral facets [19], but Enrique and coworkers observed a higher-index lateral facets{250}, and predicted a plausible transition from the {250} to {110} [20]. This is very probably relevant to the two-stage growth model above, in which nanorods before and after the TP have different type of lateral facets, {250} and {110}, respectively.…”
Section: Resultsmentioning
confidence: 99%